Young and out in Germany: On the youths' chances of labor market entrance in Germany - Wolfgang Franz; Joachim Inkmann; Winfried Pohlmeier; Volker Zimmermann (Universität Konstanz, Forschungsschwerpunkt Internationale Arbeitsmarktforschung, 1997)
This paper deals with the labor market entrance of young people in the Federal Republic of Germany. The main focus is on failures during this stage. First, an overview of the youth labor market in Germany is given. Then, the transition from vocational training to work is analyzed: The duration of the first spell of non-employment after completition of formal vocational training is analyzed by means of a proportional hazard function approach. Besides the strong influence of the human capital variables there is a striking effect of the family background of the youths. The following section addresses as to what extent early failures in the work history have long-lasting effects on future incomes.
Keywords: J21; C25; C41; 330